Social entrepreneurship and community development: The case study of Makwane village, Qwaqwa, Free State - Mosotoane, Thandeka Patricia (University of the Free State, 2022)
Rural communities in South Africa face many challenges that limit their ability to grow and develop. Among the most significant issues facing communities are unemployment and poverty (De Beer and Swanepoel, 2016). Despite the numerous approaches and efforts by government, NGOs, local and international organisation, achieving community development has been arduous. The high rate of joblessness and poverty have, impeded social and economic progress. Given the circumstances, it is vital to develop and carry out creative projects that might offer lasting sustainable solutions to social problems (Gordon, 2015), there is an urgent need for the design and implementation of innovative projects that can provide sustainable, long-term solutions to social problem. Community development is concerned with enhancement in the quality of life and standard of living of societies. According to Lombard & Strydom (2011), over 60% of population in South Africa live in rural areas making the country primarily rural. For this reason, community development initiatives should to be geared towards upgrading the standard of living of the communities and enabling them to sustain their development. This understanding helped South African government's focus on the rural communities. Sadly, despite the community development, efforts have failed to yield the desired outcome. This status quo as argued by Gordon (2015) has continued to result in situation in which there is clear mismatch between structures of the community and the kind of empowerment programmes targeted at them. Social entrepreneurship is a promising method to community development that goes beyond development assistance. Social Entrepreneurship initiatives are thought to have the ability to offer, long - term solutions for community development (Lombard and Strydom, 2011). The concept is one that should be considered as its practice could contribute positively towards community development in the areas of impact and sustainability. The primary thrust of this research is to explore social entrepreneurship as a potential force for community development.
Dissertation (MDS (Development Studies))--University of the Free State, 2022